Ability of Mathematical Generalisation Thinking of Mathematics Education Students - Fatra, Maifalinda; Angraini, Lilis Marina; Jatmiko, M. Anang (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractThe main objectives of this study are: 1) describing and analyzing the mathematical generalization ability of mathematics education students at State Islamic University (UIN) in Indonesia, 2) investigating the differences in mathematical generalization abilities of mathematics education students across State Islamic University (UIN) in Indonesia. The study was conducted at 6 UIN in Indonesia with a sample of 5th semester students using the survey method. The results of this study indicate that: 1) The ability of mathematical generalizations thinking of Mathematics Education students from 6 state Islamic universities in Indonesia can be seen from the average value of each sample. The average mathematical generalization of Syarif Hidayatullah State Islamic University in Jakarta is higher high than the other 5 state Islamic universities, with the average value of 61.31. 2) There is no difference in the ability of mathematical generalization thinking among mathematics educations students of State Islamic University (UIN) in Indonesia.AbstrakTujuan utama dari penelitian ini adalah: 1) mendeskripsikan dan menganalisis kemampuan generalisasi matematika siswa pendidikan matematika di Universitas Islam Negeri (UIN) di Indonesia, 2) menyelidiki perbedaan kemampuan generalisasi matematika siswa pendidikan matematika di Universitas Islam Negeri (UIN) ) di Indonesia. Penelitian ini dilakukan di 6 UIN di Indonesia dengan sampel mahasiswa semester 5 menggunakan metode survei. Hasil penelitian ini menunjukkan bahwa: 1) Kemampuan berpikir generalisasi matematika siswa Pendidikan Matematika dari 6 universitas Islam negeri di Indonesia dapat dilihat dari nilai rata-rata setiap sampel. Generalisasi matematika rata-rata dari Universitas Islam Negeri Syarif Hidayatullah di Jakarta lebih tinggi daripada 5 universitas Islam negeri lainnya, dengan nilai rata-rata 61,31. 2) Tidak ada perbedaan kemampuan berpikir generalisasi matematika di kalangan mahasiswa pendidikan matematika Universitas Islam Negeri (UIN) di Indonesia. How to Cite : Fatra, M., Angraini, L. M., Jatmiko, M. A. (2019). Ability of Mathematical Generalisation Thinking of Mathematics Education Students. TARBIYA: Journal of Education in Muslim Society, 6(1), 69-75. doi:10.15408/tjems.v5i1.12315.